Online and Offline Parameter Optimization of SCR Denitration Control in Power Plants - Jianbo Liu; Yaping Wang; Nan Zhao; Jiadong Wang (IEEE Access)
The optimization control of the selective catalytic reduction (SCR) denitrification system holds significant importance in the power generation industry. This paper presents an engineering fastest controller combined with active disturbance rejection control (EFC-ADRC) to enhance the control performance in SCR denitrification process. Compared with EFC, EFC-ADRC strategy has better performance in disturbances rejection when using the extended state observer(ESO) to compensate for uncertain disturbances. Two optimization methods are adopted including online Simultaneous Perturbation Stochastic Approximation (SPSA) and offline whale optimization algorithm (WOA), to tune the filter parameters in EFC by matching the time-varying characteristics of the process. Finally, the superior performance of the proposed control strategy in terms of set point tracking and disturbance rejection is verified through simulation experiments.